2006
DOI: 10.1007/s00347-006-1364-1
|View full text |Cite
|
Sign up to set email alerts
|

Augeninnendruck und Hornhautdicke

Abstract: Independently of the large differences in individual pressure measurements between non-contact tonometry and applanation tonometry, we found higher IOP values with non-contact tonometry in thicker corneas as compared with applanation tonometry. In thinner corneas there was a better correspondence between both methods. Thus, it seems very likely that corneal rigidity increases with corneal thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In this study, the CCT improved close to baseline at 6 months, but the re-maining small increase in thickness may be due to differences in surgical methods using superior cornea incision, relatively higher age than previous studies, differences in underlying diseases, and whether or not vitrectomy was used. Since IOP measurement is affected by CCT, IOP may be measured higher as corneal edema increases [20,33]. The increase of CCT at 1 month was approximately 20 μm, which may lead to underestimation of the IOP reduction.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the CCT improved close to baseline at 6 months, but the re-maining small increase in thickness may be due to differences in surgical methods using superior cornea incision, relatively higher age than previous studies, differences in underlying diseases, and whether or not vitrectomy was used. Since IOP measurement is affected by CCT, IOP may be measured higher as corneal edema increases [20,33]. The increase of CCT at 1 month was approximately 20 μm, which may lead to underestimation of the IOP reduction.…”
Section: Discussionmentioning
confidence: 99%
“…IOP measurement may depend on CCT,23 and the CCT of diabetic patients has been reported to be greater when compared with that of nondiabetic patients 24,25. Even with use of the noncontact tonometer, the IOP measurement is still affected by CCT 26. Thus, we may be concerned about the influence of a thick CCT on IOP measurement in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…However other studies have found that the NCT systematically overestimates by 0.12-0.58 mmHg, compared to GAT [ 15 , 16 , 18 ]. In addition, CCT may influence the NCT to a greater extent than it does GAT [ 19 ]. Patients also may squeeze their eyelids while awaiting the air puff, thereby interfering with accurate measurement using the NCT.…”
Section: Goldmann Applanation Tonometermentioning
confidence: 99%